Discriminatory Power Evaluation of Nuclear Ribosomal RNA Barcoding Sequences Through Ophiocordyceps sinensis Related Samples - Zhang, Ping; Cui, Shenghui; Ren, Xiu; Kang, Shuai; Wei, Feng; Ma, Shuangcheng; Liu, Bin (Frontiers in Microbiology, 2018)
Since the cost of Ophiocordyceps sinensis has increased dramatically and the counterfeits may have adverse effect to health, a rapid and precise species-level DNA barcoding identification system could be a potent approach and significantly enhance the regulatory capacity. The discrimination power of three subunits sequences from nuclear ribosomal RNA gene cluster were determined by Simpson's index of discrimination using 43 wild O. sinensis fruiting bodies, pure cultures, commercial mycelium fermented powder and counterfeits. The ITS sequences showed the highest variance and discrimination power among 43 samples, as determined by Simpson's index of discrimination (D = 0.972), followed by LSU (D = 0.963) and SSU (D = 0.921). ITS-2 sequences showed the highest discrimination power for 43 samples among ITS-1, ITS-2 and 5.8S region of ITS sequences. All O. sinensis samples were grouped into a unique ITS sequence cluster under 95% similarity and two O. sinensis samples and six non-O. sinensis samples showed false claims. Our data showed that the ITS region could provide accurate species identification for O. sinensis samples, especially when macroscopic and microscopic method could not be applied in the highly processed commercial products. Since the authentication of O. sinensis related products is essential to ensure its safety and efficacy, identification of O. sinensis through ITS sequence comparison or unique PCR amplification of the species specific target, such as the ITS region, should be considered in the next revision of Chinese pharmacopoeia.